Formation of Polyurethane Film Containing Silicone Polymer with Silanol Residue - Habaue, Shigeki; Takahashi, Yuto; Suzuki, Hiroaki; Takamushi, Yuki (International Journal of Biotechnology for Wellness Industries, 2017)
The silicone polymers containing a silanol residue were synthesized from silica gel, while the polyurethanes (PUs) bearing a carboxyl moiety were prepared using 2,2-bis(hydroxymethyl)propionic acid (BHMPA) as one of the diol components. The fabrication of the PU films was carried out using these two polymers, then the tensile and thermal properties were investigated. Both the amounts of the carboxyl side groups of the PU chain and the residual silanol of the silicone polymer significantly affected the mechanical property of the film, in addition, the incorporation of 3-aminopropyltrimethoxysilane (APTMS) was quite effective for enhancing the elastic modulus (E). As a result, the film prepared from the polyurethane containing the BHMPA unit with a combination of APTMS and the silicone polymer, having a proper amount of silanol groups, showed the highest effect (E = 5.36 N/mm2), while that observed for the film prepared without using BHMPA and a silicone polymer was 2.10 N/mm2. An acid-base interaction between the carboxyl moiety of the PU and amino group of APTMS occurred, while the formation of the siloxane linkage through the silylation reaction between the trimethoxysilyl group of APTMS and silanol also took place.